An Italian multicenter retrospective-prospective observational study on neurological manifestations of COVID-19 (NEUROCOVID) - Ferrarese, Carlo; Silani, Vincenzo; Priori, Alberto; Galimberti, Stefania; Agostoni, Elio; Monaco, Salvatore; Padovani, Alessandro; Tedeschi, Gioacchino (Neurological sciences, 2020)
Neurological manifestations of COVID-19 have been described in both single case reports and retrospective scanty case series. They may be linked to the potential neurotropism of the SARS-COV-2 virus, as previously demonstrated for other coronaviruses. We report here the description of a multicenter retrospective-prospective observational study promoted by the Italian Society of Neurology (SIN), involving the Italian Neurological Departments, who will consecutively recruit patients with neurological symptoms and/or signs, occurred at the onset or as a complication of COVID-19. Hospitalized patients will be recruited either in neurological wards or in COVID wards; in the latter cases, they will be referred from other specialists to participant neurologists. Outpatients with clinical signs of COVID and neurological manifestations will be also referred to participating neurologists from primary care physicians. A comprehensive data collection, in the form of electronic case report form (eCRF), will register all possible neurological manifestations involving central nervous systems, peripheral nerves, and muscles, together with clinical, laboratory (including cerebrospinal fluid, if available), imaging, neurological, neurophysiological, and neuropsychological data. A follow-up at hospital discharge (in hospitalized patients), and for all patients after 3 and 6 months, is also planned. We believe that this study may help to intercept the full spectrum of neurological manifestations of COVID-19 and, given the large diffusion at national level, can provide a large cohort of patients available for future more focused investigations. Similar observational studies might also be proposed at international level to better define the neurological involvement of COVID-19.